Percutaneous gastrostomy tube placement of the excluded gastric remnant after laparoscopic bariatric surgery in three patients - Mahmoud Ali; Ahmed Aly; Ayahallah Ahmed; Joseph Stavas (Society of Gastrointestinal Intervention, 2021)
Roux-en-Y gastric bypass (RYGB) is the most common bariatric surgery in the United States. RYGB is a successful and safe procedure that promotes weight loss, improves medical comorbidities and overall quality of life. Following RYGB, endoscopic access to the biliopancreatic limb and the excluded stomach is limited due to altered anatomy. Access to the excluded stomach maybe needed for management of complications following RYGB as gastric remnant decompression duo to biliopancreatic limb obstruction or nutritional support due to postoperative malnutrition. We report three cases of RYGB complications that necessitated percutaneous gastrostomy.